2019
DOI: 10.3390/ma13010046
|View full text |Cite
|
Sign up to set email alerts
|

High Thermal Conductivity and Anisotropy Values of Aligned Graphite Flakes/Copper Foil Composites

Abstract: Much attention has been paid to graphite flakes/copper (GFs/Cu) composites for thermal management due to their remarkable thermal properties. Most studies focus on the interface interaction between GFs and Cu in composites. However, controlling the orientation of GFs still remains a challenge. Herein, we report a reliable method to ensure consistent orientation of GFs in the composites. Firstly, the disorder GFs were well arranged on the surface of copper foil by tape casting process in the casting machine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Coinciding with its 2D structure of 2D materials, the high aspect ratio of flake graphite can also result in numerous heterogeneous interfaces inside the matrix, just like graphene, thereby limiting the improvement of the thermal conductivity of the composite. Moreover, the composites filled with 2D flake graphite also suffer from the anisotropic thermal, electricity, and dielectric properties [25,[35][36][37][38]. For example, Li et al [38] employed the squeeze casting method to fabricate graphite flakes/Al composites and found that as the graphite content varied from 40 to 70 vol%, the thermal conductivity of the composites increased from 544 to 714 W•m -1 •K -1 in the direction parallel to the plane of the graphite layers but decreased from 104 to 31 W•m -1 •K -1 in the direction perpendicular to the plane of the graphite layers, resulting from the high interfacial thermal resistance, low thermal conductivity (6 W•m -1 •K -1 ) and the anisotropy caused by the addition of flake graphite.…”
Section: Introduction mentioning
confidence: 99%
“…Coinciding with its 2D structure of 2D materials, the high aspect ratio of flake graphite can also result in numerous heterogeneous interfaces inside the matrix, just like graphene, thereby limiting the improvement of the thermal conductivity of the composite. Moreover, the composites filled with 2D flake graphite also suffer from the anisotropic thermal, electricity, and dielectric properties [25,[35][36][37][38]. For example, Li et al [38] employed the squeeze casting method to fabricate graphite flakes/Al composites and found that as the graphite content varied from 40 to 70 vol%, the thermal conductivity of the composites increased from 544 to 714 W•m -1 •K -1 in the direction parallel to the plane of the graphite layers but decreased from 104 to 31 W•m -1 •K -1 in the direction perpendicular to the plane of the graphite layers, resulting from the high interfacial thermal resistance, low thermal conductivity (6 W•m -1 •K -1 ) and the anisotropy caused by the addition of flake graphite.…”
Section: Introduction mentioning
confidence: 99%
“…The space between the square openings was 1.8 mm. With the aim of attaining greater thermal conductivity through better graphite alignment [22], the patterns were pressed at a pressure of 5 MPa. The thickness of the graphite composite patterns was 360 ± 20 µm.…”
Section: Resultsmentioning
confidence: 99%
“…Employing this approach can result in an improvement of thermal conductivity in a specific direction within the material. Varieties of strategies, such as stretching, 18,26,48–52 compressing 27,28,53–55 and shearing, 52,56–58 have been employed to align the internal structure of the materials. Typically, by stretching to a draw ratio of approximately 5, as illustrated in Fig.…”
Section: Orientation Strategiesmentioning
confidence: 99%